Quality Parameter Analysis, Antioxidant Activity, and FTIR Profile of Turmeric (Curcuma longa L.) from Medan, Sumba, and Papua - Noordam, Errol Rakhmad; Rahmat, Deni; Sandhiutami, Ni Made Dwi; Yuliana, Nancy Dewi (Jurusan Farmasi Universitas Negeri Gorontalo, 2025)
Turmeric (Curcuma longa L.) has long been used as a medicinal plant because it contains bioactive compounds with various health benefits. This research aims to analyze the quality parameters, antioxidant activity and Fourier Transform Infrared (FTIR) spectrum of turmeric originating from Medan, Sumba and Papua. The water content test shows that turmeric extract from Sumba has a water content of 8.55%, better than extracts from Medan and Papua. The highest yield was found in turmeric from Sumba (18.55%). Antioxidant activity testing shows that turmeric extract from Sumba has the strongest antioxidant activity with an IC50 value of 23.74 ppm. FTIR analysis shows the presence of hydroxyl groups (O-H) in the wave number range of 3500-3200 cm⁻¹ and C-H bonds at 3000-2800 cm⁻¹ in all samples. The results of this research show that turmeric from Sumba has better quality than turmeric from Medan and Papua.